Strengthening research ethics governance and regulatory oversight in Central America and the Dominican Republic in response to the COVID-19 pandemic: a qualitative study - Julio Arturo Canario Guzmán; Jessie Orlich; Renata Mendizábal-Cabrera; Argentina Ying; Claude Vergès; Eleonora Espinoza; Mario Soriano; Elsy Cárcamo; Briana Beltrán; Eddys Rafael Mendoza Marrero; Reyna Sepulveda; Claudia Nieto Anderson; et al. (BMC, 2022)
Abstract Background Good governance and regulatory supervision are required to conduct research in an international public health emergency context and to ensure compliance with ethical standards. The "Strengthening research ethics governance and regulatory oversight in Central America and the Dominican Republic in response to the COVID-19 pandemic" study is a regional effort in which research ethics stakeholders participated in addressing research ethics governance and preparedness response challenges to the COVID-19 pandemic in Central America and the Dominican Republic. Methods A qualitative action research study was conducted following a participatory approach. Research ethics stakeholders in Central America and the Dominican Republic were mapped; a regional webinar and three virtual workshops were conducted discussing research ethics governance, ethics review and collaborative research practice during the pandemic. A roundtable session presented results and obtained feedback on a draft of a policy to strengthen regional research ethics governance. Results Countries across Central America and the Dominican Republic are at different stages in their development of research ethics systems. Countries with more established systems before COVID-19 were better organized and prepared to respond. This finding argues against improvisation and supports further work on strengthening governance of research ethics systems. Community engagement in research ethics public policy-making is practically absent in the region. Research and research ethics collaboration schemes are lacking amongst the countries; however, there are incipient initiatives in the region, such as the Central America and Caribbean Network of Research Ethics Committees. A policy brief with recommendations on how to advance towards strengthening the governance of research ethics systems was prepared and submitted to the Central American Integration System for analysis and possible approval. Conclusion National research ethics systems in Central America and the Dominican Republic were unprepared to respond to the COVID-19 pandemic with respect to research oversight and effective collaboration. In most cases, national research ethics systems were found to be weak, and regional research collaboration was practically absent. To promote collaboration, a joint strategy needs to be developed with a regional vision towards sharing knowledge and best practices.